2014
DOI: 10.1007/s11307-014-0776-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of Partial Volume Effect Correction and 4D PET in the Quantification of FDG Avid Lung Lesions

Abstract: Purpose: The aim of this study is to assess a software-based method with semiautomated correction for partial volume effect (PVE) to quantify the metabolic activity of pulmonary malignancies in patients who underwent non-gated and respiratory-gated 2-deoxy-2-[ 18 F]fluoro-D-glucose (FDG)-positron emission tomography (PET)/x-ray computed tomography(CT). Procedures: The study included 106 lesions of 55 lung cancer patients who underwent respiratory-gated FDG-PET/CT for radiation therapy treatment planning. Volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Satoh et al (31) reported that metabolic tumor volume, in addition to SUV max , was significantly associated with outcomes following SBRT in lung cancer. Generally, the SUV max of lung tumors is affected by the partial volume effect due to its respiratory movement, and a previous study (32) has attempted to correct this effect by using four-dimensional PET/CT. Salavati et al (32) demonstrated that semi-automated correction for the partial volume effect improved the accuracy of FDG quantification for malignant lesions of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Satoh et al (31) reported that metabolic tumor volume, in addition to SUV max , was significantly associated with outcomes following SBRT in lung cancer. Generally, the SUV max of lung tumors is affected by the partial volume effect due to its respiratory movement, and a previous study (32) has attempted to correct this effect by using four-dimensional PET/CT. Salavati et al (32) demonstrated that semi-automated correction for the partial volume effect improved the accuracy of FDG quantification for malignant lesions of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, issues related to respiratory cycle are very complicated and cannot be readily overcome by adopting gating approaches described in the literature. 13 In contrast to cardiac cycle, which is regular in nature, respiratory motion is very irregular and varies considerably from breath to breath and therefore, attempts to improve spatial resolution of PET for imaging pulmonary or cardiac disorders have been unsatisfactory. The combination of respiratory motion with cardiac contractions makes it almost impossible to measure precise levels of tracer concentration in coronary arteries.…”
mentioning
confidence: 99%
“…By targeting arterial plaque glycolysis, a surrogate of arterial inflammation and hypoxia [1,2], 18 F-FDG PET/CT imaging can potentially detect and quantitate arterial inflammation [2,3], evaluate response to treatment [4,5], and predict risk for cardiovascular events [6]. Despite several promising studies in the literature [7][8][9][10], 18 F-FDG PET/CT imaging of arterial inflammation suffers from significant limitations which relates to partial volume effects (PVE) and to the low resolution of PET [11]. PVE is a well-known phenomenon and results in underestimation of the true quantity of radiotracer on PET images.…”
mentioning
confidence: 99%
“…We evaluated the impact of PVE correction with contrastenhanced CT (CECT) assistance on quantification of arterial wall 18 F-FDG uptake at different imaging time-points. In addition, we evaluated the correlations between PVE-corrected measurements and other measurement indices of vessel wall 18 F-FDG uptake.…”
mentioning
confidence: 99%
See 1 more Smart Citation